THE ANALYSIS OF TEACHERS’ LESSON PLAN IN IMPLEMENTING THEME-BASED INSTRUCTION FOR TEACHING ENGLISH TO YOUNG LEARNERS - Septi Sesiorina (Journal of English and Education, 2014)
Lesson plan is an important part of instruction which consists of some aspects (Goals, Objectives, Activities, Media, and Assessments). This paper reports the investigation of the aspects taken in the lesson plan in implementing Theme-Based instruction. As many as 15 lesson plans, written by two English teachers in primary school, were analyzed using qualitative method and descriptive case study as its framework. The data were obtained from document analysis. Theories from Cameron (2001), Moon (2000), Brown (2001), and Richards (2001) were adapted in analyzing the documents. The results showed that the lesson plans contained the necessary aspects, and the activities resembled Theme-Based instruction. However, improvements are needed in composing Behavioral Objectives, encouraging students’ responsibility, and producing learning outcomes.  Keywords: lesson plan, theme-based, young learners